HEALTH CARE WASTE MANAGEMENT PRACTICES IN THE HOSPİTALS OF TABUK CITY - Ammakiw, Christina L.; Balicag, Judith S.; Odiem, Marymina P. (European Scientific Journal, ESJ, 2014)
The study determined the frequency of practice of the health care waste management practices on segregation, minimization, collection, storage, transport, disposal and treatment in the hospitals in Tabuk City. The study utilized a descriptive cross-sectional design. Interviews and ocular surveys/on-site observation, and the interviewer-administered questionnaire were utilized to gather data from the head nurse, waste handler during collection, waste handler during transport and waste manager. Data collected were treated using a five point Likert scale, and quantified using the frequency count, ranking, percentage and the Weighted Mean. The revealed that the health care wastes management practices are sometimes implemented in the hospitals in Tabuk City; segregation of wastes was generally often practiced, however, the use of plastic bags/plastic-lined cardboard boxes/leak-proof as containers of infectious and pathological wastes was seldom practiced. Waste minimization was often practiced, but composting was seldom practiced. Waste collection was sometimes practiced, but the collection of general wastes every shift and collection of biohazard wastes every shift was seldom practiced by the respondents. Waste storage and waste transport were sometimes practiced by the hospitals; but labeling properly all bags/containers with basic information of content, written or attached on the bag, and using transport vehicles exclusively for HCW were never practiced. Waste disposal was sometimes practiced, but offsite disposal exclusively for HCW was never practiced. Waste treatment was seldom practiced. Treating HCW before disposal, onsite treatment and using chemical disinfection as a type of treatment were seldom practiced while categorizing HCW when treating and treating wastewater prior to discharge off-site” were never practiced. From the conclusive results, the following recommendations were formulated: There is a need for the DOH to monitor regularly the management of health care wastes in each hospital 1. For waste segregation, in the use of labels and color coding scheme, all body fluids and excreta should be disposed in the infectious category. 2. Waste minimization through source reduction and recycling not only of plastics but also other recyclable materials such as papers 3. Strengthen the practice of composting 4. Due to the lack of appropriate storage area, collection and transport of biohazard waste should be done daily. 5. The city government should propose a separate disposal site for all healthcare wastes and set limit to public access to decrease the risk of infectious diseases 6. Burial pits should be lined with material of low permeability, such as clay, to prevent groundwater contamination. However, burial pits are recommended if they are located within the premises of the establishment. Encapsulation is the best method for disposal of sharps and should be practiced. 7. Waste treatment should be done to all infectious wastes. 8. The KASC Midwifery Department can initiate and conduct education and information campaign (IEC) for the hospital personnel, patients and guests at least once a year